Phytoremediation potential of Raphanus sativus L. for lead contaminated soil - Hamadouche, Nadia Ait (Acta Biologica Szegediensis, 2012)
Phytoremediation is an emerging technology that employs the use of higher plants for the clean up contaminated environment. Phytoextraction, the use of plants to extract toxic metals from contaminated soils, has emerged as a cost-effective, environment-friendly clean up alternative. Pot culture experiments using radish (Raphanus sativus L.) was performed to investigate lead (Pb) phytotoxic effects on antioxidant enzymes and other early warning biomarkers of soil Pb exposure. The study included an assessment of heavy metal accumulation in root, shoot and leaf, effect of lead stress on growth parameter (root length, root and shoot dry weight), photosynthetic pigment content, bioaccumulation coefficient (BAC) and the activity of anti-oxidant enzymes. Results demonstrated that efficient Pb uptake was observed by the roots in contaminated plants. Root growth was higher in control plants, as compared to the contaminated. Lead exposure also influenced biochemical and physiological parameters. Administration of excess of lead was followed by an increase of Pb accumulation in leaves, and associated symptoms of toxicity. Typical symptoms of Pb toxicity developed 30 days after the beginning of treatment. Chlorophyll concentration was decreased in response to heavy metal toxicity. Activity of anti-oxidative enzymes e.g. peroxidase and catalase were increased in response to oxidative stress. Atomic absorption spectrophotometer (AAS) was used for analysis of heavy metal in soil and plant samples. The results of this research showed that radish are hyperaccumulator plants that can concentrate heavy metals in their different parts, thus they can be used for remediation of polluted area. Study also showed that potential of metal accumulator plants for extraction of metal from soil occur up to a certain level of concentration, after that when the concentration of metal increased the phytoextraction rate of metal or bioaccumulation coefficient (BAC) were decreased.